Translation of dynamic contrast-enhanced imaging onto a magnetic resonance-guided linear accelerator in patients with head and neck cancer - Michael J. Dubec; Michael Berks; James Price; Lisa McDaid; John Gaffney; Ross A. Little; Susan Cheung; Marcel van Herk; Ananya Choudhury; Julian C. Matthews; Andrew McPartlin; Geoff J.M. Parker; et al. (Physics and Imaging in Radiation Oncology)
Background and purpose: Magnetic resonance imaging – linear accelerator (MRI-linac) systems permit imaging of tumours to guide treatment. Dynamic contrast enhanced (DCE)-MRI allows investigation of tumour perfusion. We assessed the feasibility of performing DCE-MRI on a 1.5 T MRI-linac in patients with head and neck cancer (HNC) and measured biomarker repeatability and sensitivity to radiotherapy effects. Materials and methods: Patients were imaged on a 1.5 T MRI-linac or a 1.5 T diagnostic MR system twice before treatment. DCE-MRI parameters including Ktrans were calculated, with the optimum pharmacokinetic model identified using corrected Akaike information criterion. Repeatability was assessed by within-subject coefficient of variation (wCV). Treatment effects were assessed as change measured at week 2 of radiotherapy. Results: 14 patients were recruited (6 scanned on diagnostic MR and 8 on MRI-linac), with a total of 24 lesions. Baseline Ktrans estimates were comparable on both MR systems; 0.13 [95 %CI: 0.10 to 0.16] min−1 (diagnostic MR) and 0.15 [0.12 to 0.18] min−1 (MRI-linac). wCV values were 22.6 % [95 % CI: 16.2 to 37.3 %] (diagnostic MR) and 11.7 % [8.4 to 19.3 %] (MRI-linac). Combined cohort increase in Ktrans was significant (p < 0.01). Similar results were seen for other DCE-MRI parameters. Conclusions: DCE-MRI is feasible on a 1.5 T MRI-linac system in patients with HNC. Parameter estimates, repeatability, and sensitivity to treatment were similar to those measured on a conventional diagnostic MR system. These data support performing DCE-MRI in studies on the MRI-linac to assess treatment response and adaptive guidance based on tumour perfusion.